2022
DOI: 10.1002/anie.202200187
|View full text |Cite
|
Sign up to set email alerts
|

Operando Imaging of Chemical Activity on Gold Plates with Single‐Molecule Electrochemiluminescence Microscopy

Abstract: Classical electrochemical characterization tools cannot avoid averaging between the active reaction sites and their support, thus obscuring their intrinsic roles. Single-molecule electrochemical techniques are thus in high demand. Here, we demonstrate superresolution imaging of Ru(bpy) 3 2 + based reactions on Au plates using single-molecule electrochemiluminescence microscopy. By converting electrochemical signals into optical signals, we manage to achieve the ultimate sensitivity of single-entity chemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Super-resolution images of these descriptors are provided in Figure 13A. 348 This study revealed that the more active sites, characterized by higher reaction rate constants, are located at the edges of the catalyst. By comparing the TOF maps, constructed at different potentials, they also highlighted the formation of Au oxide on the catalysts at higher overpotential, resulting in a decrease in activity.…”
Section: Electron Transfermentioning
confidence: 92%
See 1 more Smart Citation
“…Super-resolution images of these descriptors are provided in Figure 13A. 348 This study revealed that the more active sites, characterized by higher reaction rate constants, are located at the edges of the catalyst. By comparing the TOF maps, constructed at different potentials, they also highlighted the formation of Au oxide on the catalysts at higher overpotential, resulting in a decrease in activity.…”
Section: Electron Transfermentioning
confidence: 92%
“…ECLM is then ideal for imaging objects or reactions nearby the electrode region with single photon sensitivity. 345,348…”
Section: Methodologies For Quantitative Image Analysismentioning
confidence: 99%
“…Recently, optical microscopy has provided a visualized tool to directly observe ECL phenomena including the electron transfer rate at the electrodesolution interface and species diffusion in the vicinity of the electrode. [38][39][40][41][42] The versatile microscopy technique has been used ranging from ECL mechanism discussion to biological applications. [43][44][45][46] For example, the thickness of the ECL layer (TEL) was depicted by ECL microscopy, 44 which was further used for not only the selective imaging of cell-matrix and cell-cell junctions but also the investigation of the chemical lens effect.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] This is due to ECL's high sensitivity and selectivity, exceptionally low background, high linear dynamic range, chemical stability of the luminophore, straightforward conjugation of the ECL-label to biomolecules, and temporal resolution. [18][19][20][21][22] ECL involves an electron transfer process at the surface of an electrode, followed by a sequence of reactions, which eventually leads to the excited state of the luminophore. 23,24 The relaxation of this excited state results in photon emission.…”
Section: Introductionmentioning
confidence: 99%